Kinetics and Mehanism of Oxidation of Arometic acetals by Acidic Pyridium Chlorochromate - Ramakrishnan, P.S. (Asian Journal of Chemistry, 2010)
The kinetics of oxidation of aromatic acetals by pyridinium cblorocbromate (PCC) have been studied. The reaction is first order each in [PCC] and [Acetal]. With an increase in the amount of acetic acid in its aqueous mixture, the rate increases. The reaction does not induce polymerisation of acrylonitrile. The presence of electronwithdrawing substituents in the benzene ring enhances the rate of oxidation. The rate of oxidation depends on the nature of alkyl group. The reaction rates have been studied at different temperatures and the activation parameters calculated.